Three-dimensional whole-body descriptions
The subjects for this study were swimmers at the 1991 Perth World Championships. Trends in body factors and some arm features were reported for the different strokes. Summary: The streamlining of the body is of paramount importance in all strokes. The body is the major contributor to resistance. Its shape creates passive resistance something which cannot be altered immediately. However, inefficient streamlining, unnecessary up and down or sideways movements, increases active resistance which slows the swimmer. The stabilization and orientation of the body is the central characteristic of good swimming. If the body is "out of position" it will not allow correct arm actions to occur which, in turn, result in less propelling efficiency. It is reasonable to assert that if the body position of a swimmer is not maximally streamlined, the swimmer will not be able to swim fast. In the two symmetrical strokes, the body should be as streamlined as possible but it has to move to create a fast propulsive wave action. That action is not necessarily big. An exaggeration of the wave action segments will actually slow the cycle time to the point of not contributing to the force and even creating unnecessary resistance. Because a wave action is beneficial it does not necessarily follow that a bigger action is more beneficial. It would be more prudent for a coach to minimize the wave action, for at least then, the swimmer will be streamlined.